Evaluation of the wound healing potential of Aloe vera-based extract of Nerium oleander - (:unkn) unknown (My University, 2017)
0

OBJECTIVE:Nerium oleander (Apocynaceae) and Aloe vera (Liliaceae) are among the widely used herbal remedies for treating skin diseases and possess numerous activities such as antibacterial, antiviral, antifungal, and antioxidant. The aim of this study was to investigate the possible wound healing effect of Aloev era-based extract of the N. oleander leaf (NAE-8®) based on its antioxidant, anti-inflammatory, and DNA repair capacity along with histological changes and to compare them with the traditional silver sulfadiazine treatment (SSD).METHODS: Twenty-four Wistar albino rats were randomly grouped as follows: i) control, ii) burn alone (burn), iii) burn with topical NAE-8® (burn+NAE-8®) treatment, and iv) burn with topical 1% silver sulfadiazine (burn+SSD) treatment. All groups received their related topical application twice a day for 14 consecutive days. Upon completion of the experimental protocol, trunk blood and skin tissues were collected for measuring malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO), tumor necrosis factor alpha (TNF-?), interleukin-1? (IL-1?), %DNA in the tail (%DNAT) levels along with histological examinations.RESULTS: Thermal injury-induced alterations in MDA, GSH, MPO, TNF-?, IL-1?, and %DNAT levels were significantly reversed by NAE-8® treatment. These ameliorative effects were also supported by histological findings.CONCLUSION: Findings of the present study suggest that NAE-8® is a promising remedy for treating skin burn injury.
Keywords: Genel ve Dahili Tıp